解方程:(2x-3)平方-(x+1)平方=0 ,4(x-2)平方=9(1-x)平方

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/16 13:45:06
解方程:(2x-3)平方-(x+1)平方=0 ,4(x-2)平方=9(1-x)平方

解方程:(2x-3)平方-(x+1)平方=0 ,4(x-2)平方=9(1-x)平方
解方程:(2x-3)平方-(x+1)平方=0 ,4(x-2)平方=9(1-x)平方

解方程:(2x-3)平方-(x+1)平方=0 ,4(x-2)平方=9(1-x)平方
(2x-3)平方-(x+1)平方=0
(3x-2)(x-4)=0
x=2/3或x=4
4(x-2)平方=9(1-x)平方
9(1-x)平方-4(x-2)平方=0
(3-3x+2x-4)(3-3x-2x+4)=0
(-x-1)(-5x+7)=0
x=-1或x=7/5

X=4,X=-1或者X=7/5

(2x-3)²-(x+1)²=0
(2x-3)²=(x+1)²
2x-3=x+1 x=4
或3-2x=x+1 x=2/3
(2) 4(x-2)²=9(1-x)²
2(x-2)=3(1-x)
2x-4=3-3x
x=7/5
或 2x-4=3x-3
x=-1